Bereaved Elders: Transformative Learning in Late Life - Paul J. Moon (Adult Education Research Conference, 2009)
The purpose of this qualitative study was to understand older adults’ transformative learning through bereavement in late life. Nine participants were engaged in semi-structured interviews. Data analysis affirmed that perspective transformation can occur through late life bereavement characterized by an oscillatory process shaped by biographical and life stage developmental contexts.